Nationalism Education: Dialectical Relations Between Darussalam Islamic Boarding School Education and Tradition of the Manokwari Society of West Papua - Syarifah, Ma’isyatusy; Indriyani, Dian; Almachim, Ainul Churria (IJIBS, 2023)
Research refutes the opinion of Francis Fukuyama, in his book The End of History and the Last Man (2006) which states that nationalism is dead and does not need to be taught. This thesis was written to strengthen previous research which also questioned the existence of nationalism in the world of education such as Coulby and Zambeta (2007) which stated that the old ideology of nationalism which in certain aspects was universalistic, humanistic conceptualized by intellectuals, lost "truth" and the power to captivated many people in the west. A new concept is needed to strengthen nationalism education which strengthens 'national stability' in areas transitioning towards industrial culture. Dewey ( 2010 ) stated that nationalism education for students forms the characteristics of a democratic life that cannot be separated from learning. Maksu>d (2008) states that nationalism education is an effort to raise national personality and pride in the homeland. Efforts to strengthen these values cannot be denied through teaching at all levels of education. This research shows that (1 ) the ideology of nationalism needs to be taught in formal education because it is considered dead; (2) Nationalism education is the basis for strengthening the spirit of unity and nationality; (3) Strengthening nationalism through formal education (schools and Islamic boarding schools) is one of the effective steps to suppress national disintegration. The main sources of this thesis are various research results and documentation relating to the dynamics of the pesantren in Manokwari which are synonymous with Islamic studies and traditionalism, with a pluralistic society adhering to the majority Christian religion and the strength of the Free Papua Organization movement. the dealektics of the educational tradition of nationalism in the Darussalam Islamic Boarding School and the cultural traditions of the local community which are implemented in behavior and attitudes within the people of West Papua. To obtain these data, observations, interviews and documentation were carried out which were analyzed through qualitative research with a phenomenological approach.